Doktrin Penciptaan dalam Perspektif Teologi Kristen dan Relevan Bagi Iman Masa Kini (Jurnal Pendidikan Agama dan Teologi, 2025)
This article theologically analyzes the Christian doctrine of creation, highlighting the nature of God as Creator and its implications for human understanding of the world, the self, and the relationship with God. Creation is understood not merely as the initial event of the cosmos but also as God’s continuous act of sustaining, preserving, and directing all creation toward His divine purpose. Through a study of biblical texts and the reflections of classical theologians such as Augustine, Aquinas, and Calvin, this paper explores the concepts of creatio ex nihilo, the orderliness of creation, and the dignity of humanity as the image of God (imago Dei). This article also outlines how the doctrine of creation provides an ethical foundation for ecological responsibility, the sanctity of life, and respect for others in the context of contemporary challenges marked by moral crises and environmental degradation. The analysis shows that the doctrine of creation remains relevant for today’s faith, emphasizing that the world derives its meaning from God and that humanity is called to participate with God in caring for creation. Thus, this study offers a comprehensive understanding of the significance of the doctrine of creation for Christian faith and ethical practice in contemporary life.